1993
DOI: 10.1136/ard.52.8.616
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Paget's disease of bone with single dose intravenous pamidronate.

Abstract: Objectives-To assess the efficacy of a single intravenous infusion of pamidronate in Paget's disease ofbone. Methods-Fourteen patients with active Paget's disease (raised serum alkaline phosphatase, bone pain or neurological involvement) were treated with a single intravenous infusion of 105 mg pamidronate. Patients were assessed for biochemical and clinical improvement for up to two years following treatment. A further infusion was given following symptomatic relapse (pain at a known site of pagetic involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
1
5
0
3
Order By: Relevance
“…Several studies have shown the beneficial effect of this treatment, with a substantial number of patients remaining in remission for up to 18 months to two years 2 3. Our study showed the beneficial effect of even a moderate dose (60 mg) given as a single infusion in moderate to severe active Paget's disease 2.…”
supporting
confidence: 51%
“…Several studies have shown the beneficial effect of this treatment, with a substantial number of patients remaining in remission for up to 18 months to two years 2 3. Our study showed the beneficial effect of even a moderate dose (60 mg) given as a single infusion in moderate to severe active Paget's disease 2.…”
supporting
confidence: 51%
“…dosing regimens have been proposed. [21][22][23][24][25][26][27][28][29][30] The more utilized regimen is 3 to 6 i.v. infusion of 60 mg of pamidronate (Aredia ® ) at an infusion rate of 1 mg/min within 3-21 days.…”
Section: Bisphosphonates and Paget's Diseasementioning
confidence: 99%
“…21,31 Effectiveness lasts for long periods after a single cycle of therapy in relation to entity of abolition of the osseous turnover: the greater the abolition, especially if it is within the normal range, the longer the persistence of efficacy. 23,25,29,30,32 Noteworthy, clinical improvement can also include the remission of neurological complications. 33 Following the administration of pamidronate 600 mg/day orally for an average period of 9.5 months, 80% of patients normalized their AP levels; of the 20% who did not, all had a very high initial AP level before treatment started.…”
Section: Bisphosphonates and Paget's Diseasementioning
confidence: 99%
“…Infusion (60 mg/2wöchentlich/3x oder 30 mg/wöchentlich/6x) erfolgreich verwendet [24][25][26][27][28][29][30]. Infusion (60 mg/2wöchentlich/3x oder 30 mg/wöchentlich/6x) erfolgreich verwendet [24][25][26][27][28][29][30].…”
Section: Therapieunclassified